2008
DOI: 10.1089/jpm.2008.9992
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Medicine Review: Prognostication

Abstract: Prognostication, along with diagnosis and treatment, is a traditional core clinical skill of the physician. Many patients and families receiving palliative care want information about life expectancy to help plan realistically for their futures. Although underappreciated, prognosis is, or at least should be, part of every clinical decision. Despite this crucial role, expertise in the art and science of prognostication diminished during the twentieth century, due largely to the ascendancy of accurate diagnostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
211
0
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(219 citation statements)
references
References 69 publications
1
211
0
7
Order By: Relevance
“…[4][5][6] Although increasingly, studies have documented that most patients want to receive prognostic information and that truthful communication is not harmful, 7,11,12 in this large, population-based study of patients with metastatic lung or colorectal cancer, we found that many had a limited prognosis awareness soon after diagnosis, even though most of them had received chemotherapy. Our findings suggest that physician communication behaviors are associated with patients' perception of prognostic information.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…[4][5][6] Although increasingly, studies have documented that most patients want to receive prognostic information and that truthful communication is not harmful, 7,11,12 in this large, population-based study of patients with metastatic lung or colorectal cancer, we found that many had a limited prognosis awareness soon after diagnosis, even though most of them had received chemotherapy. Our findings suggest that physician communication behaviors are associated with patients' perception of prognostic information.…”
Section: Resultsmentioning
confidence: 95%
“…[1][2][3] Knowledge of prognosis is essential for terminally ill patients because prognosis awareness can influence their preferences for aggressive therapy versus supportive care. [4][5][6] Other evidence suggests that truthful communication about prognosis is not harmful. 7 Several studies have documented that patients with metastatic cancers tend to overestimate their prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…The idea that a simple once a day administration regime will foster adherence is certainly beguiling, but the research evidence is more nuanced. A number of systematic reviews 1,2 and a recent meta-analysis 3 have addressed the relationship between adherence and dose frequency, and their findings do indeed suggest an inverse gradient between dose frequency and adherence. The meta-analysis by Coleman and colleagues 3 was methodologically more advanced and focused on oral dosage forms where adherence was assessed by electronic monitoring.…”
Section: Editorials Editorialmentioning
confidence: 99%
“…Glare and Sinclair demonstrated quantitatively the subservience of 'prognosis' to 'diagnosis' and 'therapy' by measuring the number of hits in a PubMed search; the number of hits for prognosis was eight to nine times less than those for the other two terms. 3 To an extent, the disappearance of 'prognosis' could be ascribed to the fact that the term is mostly associated with an answer to the question "Doc, how much time do I have? ", 4 a question only one in three physicians discusses with their patients 5 -and avoided because physicians find themselves ill-prepared for prognostication and find it stressful to make predictions.…”
mentioning
confidence: 99%
“…1 Predicting survival, in particular, is important as it may prove the deciding factor in decisions to pursue aggressive treatments, 2 to change goals of care, or decisions to leave the hospital. 3 Patients with limited predicted survival, in particular, may choose to forego disease oriented treatments and to seek care in settings other than acute care hospitals.…”
mentioning
confidence: 99%